Ancient Naples A Documentary History Origins to C. 350 CE. - Taylor, Rabun M. (A Documentary History of Naples Ser., 2021)
Drawing on historical, literary, and archaeological sources, this volume provides a cultural, economic, material, and political history of the city of Naples, Italy from its beginnings as a Greek settlement in the eighth century BCE to the reign of the emperor Constantine in the fourth century CE.